Kesesuaian Sarana dan Prasarana Perpustakaan Kantor Perwakilan Bank Indonesia Provinsi Aceh Berdasarkan Standar Nasional Perpustakaan Nomor 14 Tahun 2017 - Alza Taufiqur Rahman; Umar Bin Abdul Aziz; Nurul Rahmi (Indonesian Journal of Library and Information Science, 2023)
The article discusses the availability of Special Library facilities and infrastructure based on Library National Standards (SNP) Number 14 of 2017 at the Library of the Aceh Provision of Bank Indonesia Representative Office. The purpose of this study was to determine the availability of facilities and infrastructure in the Aceh Province Bank Indonesia Representative Office Library based on National Library Standards (SNP) number 14 of 2017 concerning special library standards. This research uses a qualitative approach with descriptive methods. Data collection techniques were carried out by observation, interviews and documentation. The results showed that the availability of facilities and infrastructure in the Aceh Province Bank Indonesia Representative Office Library was not in accordance with the National Library Standards (SNP) Number 14 of 2017. In the building specifications for the Bank Indonesia Representative Office Library in Aceh Province, it was not in accordance with standards starting from a building area of ​​only 68m2 the library should have a building with an area of ​​200m2, it does not yet have a work space, so it is not up to standard. In addition, there are still some furniture that are not suitable, namely reading tables and work tables. In fulfilling the availability of facilities and infrastructure in accordance with the National Library Standards (SNP) Number 14 of 2017.